The material requirements planning system for vacuum manufacturer - Mohd Nor, Norasmiha; Abdul Ghani, Muhammad Hanif; Umar Rashid, Muhammad Aiman Ifqin; Young, Ke Xin; Heng, Chien Ying; Jamzuri, Amelia Yuzni; Cheam, Kai Wen (Penerbit UTHM, 2020)
Production planning and control (PPC) is an advance tool that helps to determine the flow which includes the use of human resources, materials, machines, etc. PPC is a technique to plan each individual operation in long-term series. It helps to make the most correct decisions at the right time and position to achieve maximum efficiency. At the same time, PPC are responsible for coordinating different processes, departments and personnel to ensure that they are all using their time efficiently and economically. The goal of PPC is to ensure the safety and economy of the production process, to effectively use the factory to maximize productivity, to maximize efficiency through appropriate coordination in the production process, to minimize labor mobility, and so on (Clothing Industry, 2017).